Pengaruh Locus of Control, Kepribadian, dan Motivasi terhadap Prestasi Mahasiswa Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang - Kurniawan Budi Prastyo; Vincy Yascha Afrizzo Crownecy; Rauly Sijabat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The purpose of this research is to test and analyze the influence of the Locus Of Control, personality and motivation on the performance of students of the Faculty of Economics and Business of PGRI University Semarang. This type of research uses quantitative research with primary data sources to find out the population of this survey is a student of the faculty of economics and business of the University PGRI Semarang using a sample of 30 responded that represents students of School of Business and Economics.This research uses the help of IBM SPSS Statitic Version 26 using double linear refraction. The results show that:(1) the Locus Of Control has no significant impact on performance,(2) the personality has a significant influence on achievement,3) the motivation of a partial influence is significant on performance.